Wear-resistant polyethylene composite material for marine organism prevention device and preparation method of wear-resistant polyethylene composite material

By using combined injection molding technology of UiO-66(Zr)@PEI wear-resistant filler and polyvinyl matrix in the anti-sea biological device, a high mechanical strength and wear-resistant polyethylene composite material was prepared, which solved the problem of easy destruction of the anti-sea biological device in the prior art in harsh marine environments and realized the effective application in the offshore wind power anti-sea biological device.

CN119529410APending Publication Date: 2025-02-28GUANGDONG ENERGY GROUP SCIENCE & TECHNOLOGY RESEARCH INSTITUTE CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411853128.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Existing sea-proof biological devices are susceptible to damage in harsh marine environments and are difficult to meet the long-term environmental protection requirements for offshore wind power to prevent sea-proof biological removal.

Method used

UiO-66(Zr) metal organic frame is used as the basis, and UiO-66(Zr)@PEI wear-resistant filler is prepared by linear polyethyleneimine coating modification, and mixed with polyvinyl matrix, capacity-enhancing modifier and antioxidant to prepare polyethylene composite materials with excellent mechanical properties and high wear resistance.

Benefits of technology

It significantly improves the mechanical strength and wear resistance of the material, can be used stably in harsh marine environments, and is suitable for offshore wind power marine biological devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529410A_ABST
    Figure CN119529410A_ABST
Patent Text Reader

Abstract

The invention provides a wear-resistant polyethylene composite material for a marine organism prevention device and a preparation method of the wear-resistant polyethylene composite material, a UiO-66 (Zr) metal organic framework is adopted as a basis, and linear polyethyleneimine is used for coating modification to obtain a UiO-66 (Zr) coated PEI wear-resistant filler; and then the UiO-66 (Zr)-coated PEI wear-resistant filler, a polyethylene matrix, a compatibilization modifier and an antioxidant are subjected to mixed injection molding to obtain the polyethylene composite material with good mechanical properties and excellent wear resistance, and the polyethylene composite material is suitable for being widely applied to offshore wind power marine organism prevention devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of marine biofilm prevention, and in particular to a wear-resistant polyethylene composite material for a marine biofilm prevention device and a preparation method thereof. Background Art

[0002] After more than 20 years of development, my country's offshore wind power technology has become increasingly mature and has now entered the stage of large-scale development, with a very broad development prospect. However, after the steel pile foundation of offshore wind power and underwater structures such as underwater conductors are installed in place, marine organisms will attach to their surfaces and continue to grow. Especially in subtropical and tropical waters, the attachment of marine organisms to the conductors is more significant, with a thickness of 20 to 60 cm and a depth of 50 m. Environmentally friendly and long-term removal methods are urgently needed.

[0003] CN218085969U discloses a device for preventing marine biological attachment and an offshore supporting foundation. The device for preventing marine biological attachment is used to form a polygonal ring around the outer wall of a protected body. The device for preventing marine biological attachment comprises at least one impact roller and at least one connecting device, wherein the at least one impact roller has at least one connecting female part; the at least one connecting device has at least one connecting male part, at least one flexible part and / or at least one arc-shaped part; the at least one connecting male part is rotatably clamped in the at least one connecting female part; the at least one impact roller and the at least one connecting device are connected in sequence through at least one connecting female part and at least one connecting male part to form a polygonal ring structure; the device for preventing marine biological attachment can form a polygonal ring around the outer side of a protected steel structure such as a pile leg of an offshore oil platform, and the overall installation is convenient, safe and reliable, and cost-saving.

[0004] CN218537052U discloses a marine growth prevention ring, pile and offshore support foundation, comprising at least one collision roller and at least one serial connection body, wherein the middle part of the at least one collision roller has at least one first serial connection hole; the at least one serial connection body is configured to serially connect the at least one collision roller through the at least one first serial connection hole and form a closed ring structure; at least one spacing component is arranged between the at least one adjacent collision rollers, and the at least one serial connection body is also configured to pass through the at least one spacing component; the at least one collision roller and / or at least one spacing component are configured to be rotatable on the at least one serial connection body; the marine growth prevention ring can surround the outside of the protected steel structure such as the pile leg of the offshore oil platform to form a polygonal ring, and the overall installation is convenient, safe and reliable, and cost-saving.

[0005] CN220598313U discloses a density-controllable marine growth prevention device, comprising a plurality of connecting devices and a plurality of roller bodies; the roller bodies and the connecting devices are spaced apart, and the plurality of roller bodies are sequentially connected into a ring shape through the plurality of connecting devices; the roller bodies are provided with adjusting members, and the adjusting members are used to adjust the average density of the roller bodies, so that the roller bodies float on the water surface or suspend between the water surface and the bottom of the water; the density-controllable marine growth prevention device can precisely control the overall density according to the local seawater density and the use environment, so that the device can achieve the effect of floating on the water surface or suspending underwater, thereby meeting the anti-fouling requirements of different areas of the conductor frame, pile legs and other components.

[0006] The above anti-marine growth devices all use the ups and downs of the waves and the driving of the submarine currents to remove marine growth on the offshore wind power pile foundation and the conductor frame. However, this device has very high requirements for special materials. Conventional polymer materials are often damaged in harsh marine environments such as typhoons. Therefore, it is necessary to develop special materials with high strength and high wear resistance. Summary of the invention

[0007] In view of the problems existing in the prior art, the present invention provides a wear-resistant polyethylene composite material for anti-marine biological devices and a preparation method thereof. The UiO-66(Zr) metal organic framework is used as a basis, and a linear polyethyleneimine is used for coating and modification to obtain a UiO-66(Zr)@PEI wear-resistant filler. The UiO-66(Zr)@PEI wear-resistant filler is then mixed with a polyethylene matrix, a volume-increasing modifier and an antioxidant for injection molding to obtain a polyethylene composite material with good mechanical properties and excellent wear resistance, which can meet the use requirements in harsh marine environments.

[0008] To achieve this object, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a wear-resistant polyethylene composite material for an anti-marine biological device, wherein the wear-resistant polyethylene composite material for an anti-marine biological device comprises a UiO-66(Zr)@PEI wear-resistant filler, a polyethylene matrix, a volume-increasing modifier and an antioxidant; the UiO-66(Zr)@PEI wear-resistant filler is based on a UiO-66(Zr) metal organic framework and is modified using a linear polyethyleneimine; the volume-increasing modifier comprises a polyolefin having an anhydride group.

[0010] The wear-resistant polyethylene composite material for the anti-marine biological device of the present invention is based on the UiO-66 (Zr) metal organic framework, and is further coated and modified by linear polyethylene imine to prepare UiO-66 (Zr) @ PEI; the UiO-66 (Zr) modified by linear polyethylene imine not only has the high wear resistance of the zirconium-based MOF, but also grows a large number of primary and secondary amine groups on the periphery of the UiO-66 (Zr) nanoparticles. Compared with small molecule amine modifiers, the linear polyethylene imine with a larger molecular weight has better compatibility with high-density polyethylene. In addition, the present invention also adds a polyolefin with anhydride groups as a volume-increasing modifier. In the amorphous region of the polyethylene matrix, a large number of amine groups on the surface of UiO-66 (Zr) @ PEI are connected to the anhydride groups in the volume-increasing modifier through amide chemical bonds, and the polyethylene chains in the volume-increasing modifier are miscible with the high-density polyethylene matrix, thereby improving the mechanical strength and wear resistance of the material in the amorphous region at the same time, and is suitable for use in offshore wind power anti-marine biological devices.

[0011] The wear-resistant polyethylene composite material for the marine biological prevention device of the present invention adopts linear polyethyleneimine as a raw material, thereby avoiding the problem of using dendritic polyethyleneimine with high viscosity as a raw material, which leads to processing difficulties.

[0012] Preferably, the density of the polyethylene matrix is ​​0.94-0.96 g / cm 3 , for example, it can be 0.94 g / cm 3 , 0.943g / cm 3 , 0.945g / cm 3 , 0.95g / cm 3 、0.955g / cm 3 , 0.958g / cm 3 or 0.96g / cm 3 The above range is not limited to the listed values, and other values ​​not listed within the above range are also applicable.

[0013] Preferably, the compatibilizing modifier comprises polyethylene grafted with maleic anhydride.

[0014] Preferably, the molecular weight of the linear polyethyleneimine is 300-1800, for example, 300, 500, 800, 1200, 1500 or 1800, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0015] The present invention preferably uses linear polyethyleneimine with a molecular weight of 300 to 1800, which has a density of 0.94 to 0.96 g / cm 3 The compatibility of polyethylene matrix is ​​good.

[0016] Preferably, the antioxidant includes antioxidant 1010 or antioxidant 168.

[0017] Preferably, the mass ratio of the UiO-66(Zr)@PEI wear-resistant filler, polyethylene matrix, volume-increasing modifier and antioxidant is (1-6):100:(3-6):0.1, for example, it can be 1:100:3:0.1, 2:100:3.5:0.1, 3:100:4:0.1, 4:100:4.5:0.1, 5:100:5:0.1 or 6:100:6:0.1, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0018] The present invention preferably has a mass ratio of the UiO-66(Zr)@PEI wear-resistant filler, polyethylene matrix, volume-increasing modifier and antioxidant of (1-6):100:(3-6):0.1, thereby ensuring that the obtained wear-resistant polyethylene composite material for anti-marine biological device has excellent mechanical properties and wear resistance.

[0019] When the mass of UiO-66(Zr)@PEI wear-resistant filler increases, the tensile strength and bending strength of the wear-resistant polyethylene composite material for anti-marine biological devices are significantly improved simultaneously, and the friction coefficient is also greatly improved.

[0020] In a second aspect, the present invention further provides a method for preparing the wear-resistant polyethylene composite material for the marine biological prevention device as described in the first aspect, the preparation method comprising the following steps:

[0021] S1. Preparation of UiO-66(Zr)@PEI wear-resistant filler: UiO-66(Zr) is prepared by reacting zirconium tetrachloride and terephthalic acid, and then UiO-66(Zr) is coated with PEI to obtain UiO-66(Zr)@PEI wear-resistant filler;

[0022] S2. Preparation of wear-resistant polyethylene composite material for anti-marine growth device: mixing the UiO-66(Zr)@PEI wear-resistant filler with a polyethylene matrix, a volume-increasing modifier and an antioxidant, and performing injection molding using an injection molding machine to obtain the wear-resistant polyethylene composite material for anti-marine growth device.

[0023] The preparation method of the wear-resistant polyethylene composite material for the anti-marine biological device of the present invention is simple to operate and has mild reaction conditions. UiO-66(Zr) is coated with PEI to prepare UiO-66(Zr)@PEI wear-resistant filler. The schematic diagram of its preparation route is as follows: Figure 1As shown in the figure, a large number of primary and secondary amine groups on the linear polyethyleneimine on the surface of UiO-66(Zr)@PEI can react with polyolefins having anhydride groups to form chemical amide bonds. In addition to reacting with UiO-66(Zr)@PEI to form amide bonds, the polyolefins having anhydride groups have polyethylene main chains that are miscible with the polyethylene matrix to form chemical bonding sites between organic and inorganic materials in the mixed system, which greatly improves the mechanical strength and wear resistance of the wear-resistant polyethylene composite material for marine biological prevention devices, and is suitable for large-scale promotion and application in offshore wind power marine biological prevention devices.

[0024] Preferably, the specific steps of preparing UiO-66(Zr)@PEI wear-resistant filler in S1 include:

[0025] S1.1, preparing UiO-66 (Zr) powder: zirconium tetrachloride, terephthalic acid and a first solvent are mixed, and hydrochloric acid with a concentration of 1 to 6 mol / L is added after stirring, and a first ultrasonic treatment, a first drying, a first cooling, a first solid-liquid separation and a first washing are performed in sequence to obtain a washed product; the washed product is immersed in a methanol solution, and a second solid-liquid separation, a second washing and a second drying are performed to obtain UiO-66 (Zr) powder;

[0026] S1.2, preparation of UiO-66(Zr)@PEI wear-resistant filler: dissolving the UiO-66(Zr) powder in a second solvent, and performing a second ultrasonic treatment; adding linear polyethyleneimine dropwise under stirring, and sequentially performing a third ultrasonic treatment, a second cooling, a third washing, a third solid-liquid separation, and a third drying to obtain the UiO-66(Zr)@PEI wear-resistant filler.

[0027] The first ultrasonic treatment, the second ultrasonic treatment and the third ultrasonic treatment in the present invention mainly disperse the reaction materials; the first drying, the second drying and the third drying are carried out at a temperature of 100-120° C. for 24 hours; the first cooling and the second cooling are both carried out at room temperature of 20-30° C.

[0028] In the present invention, the first solid-liquid separation, the second solid-liquid separation and the third solid-liquid separation can be filtration, sedimentation or centrifugation, etc., preferably filtration.

[0029] S1.1 of the present invention, preparation of UiO-66 (Zr) powder: zirconium tetrachloride, terephthalic acid and a first solvent are mixed, stirred and then added with hydrochloric acid having a concentration of 1 to 6 mol / L, for example, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L or 6 mol / L, etc., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0030] Preferably, the molar ratio of zirconium tetrachloride to terephthalic acid in S1.1 is 1:1 to 1:3, for example, 1:1, 1:1.5, 1:1.8, 1:2, 1:2.5 or 1:3, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0031] The present invention preferably has a molar ratio of zirconium tetrachloride to terephthalic acid of 1:1 to 1:3, which has the advantage of high product purity. When the molar ratio of zirconium tetrachloride to terephthalic acid is less than 1:3, excessive acid will be present in the product; when the molar ratio of zirconium tetrachloride to terephthalic acid is greater than 1:1, excessive zirconium oxide will be present in the product.

[0032] Preferably, the first solvent comprises DMF solvent.

[0033] Preferably, the first washing is performed using DMF solvent, and the washing is repeated 3 to 5 times, for example, 3 times, 4 times or 5 times.

[0034] Preferably, the second solvent in S1.2 comprises ethanol solvent.

[0035] Preferably, the drop rate of the linear polyethyleneimine in S1.2 is 20 to 40 drops per minute, for example, 20 drops, 22 drops, 25 drops, 30 drops, 35 drops or 40 drops, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0036] When the linear polyethyleneimine dropping rate is too fast, the polyethyleneimine coating on UiO-66(Zr) will be uneven; when the linear polyethyleneimine dropping rate is too slow, the reaction time will be prolonged.

[0037] Preferably, the amount of linear polyethyleneimine added is 1% to 6% by mass of UiO-66(Zr), for example, it can be 1%, 1.5%, 2%, 3%, 5% or 6%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0038] The invention preferably adds 1% to 6% of the mass percentage of the linear polyethyleneimine to UiO-66(Zr), which has the advantage of uniform coating. When the amount of linear polyethyleneimine added is small, the density of amine groups on the surface of UiO-66(Zr) will be reduced, and the cross-linking density of chemical bonds will be reduced; when the amount of linear polyethyleneimine added is large, it will lead to uneven distribution and reduce the mechanical properties.

[0039] As a preferred technical solution of the present invention, the preparation method comprises the following steps:

[0040] S1.1, preparing UiO-66 (Zr) powder: zirconium tetrachloride, terephthalic acid and DMF solvent are mixed, and hydrochloric acid with a concentration of 1 to 6 mol / L is added after stirring, and the mixture is subjected to a first ultrasonic treatment, a first drying, a first cooling, a first solid-liquid separation, and a first washing with a DMF solvent, and the washing is repeated 3 to 5 times to obtain a washed product; the washed product is immersed in a methanol solution, and a second solid-liquid separation, a second washing and a second drying are performed to obtain UiO-66 (Zr) powder; the molar ratio of zirconium tetrachloride to terephthalic acid is 1:1 to 1:3;

[0041] S1.2, preparation of UiO-66 (Zr) @ PEI wear-resistant filler: dissolving the UiO-66 (Zr) powder in an ethanol solvent, and performing a second ultrasonic treatment; adding linear polyethyleneimine at a rate of 20 to 40 drops per minute under stirring, and sequentially performing a third ultrasonic treatment, a second cooling, a third washing, a third solid-liquid separation and a third drying to obtain the UiO-66 (Zr) @ PEI wear-resistant filler; the amount of the linear polyethyleneimine added is 1% to 6% by mass of UiO-66 (Zr);

[0042] S2. Preparation of wear-resistant polyethylene composite material for anti-marine growth device: mixing the UiO-66(Zr)@PEI wear-resistant filler with a polyethylene matrix, a volume-increasing modifier and an antioxidant, and performing injection molding using an injection molding machine to obtain the wear-resistant polyethylene composite material for anti-marine growth device.

[0043] In a third aspect, the present invention further provides an application of the wear-resistant polyethylene composite material for marine growth prevention device as described in the first aspect in an offshore wind power marine growth prevention device.

[0044] The wear-resistant polyethylene composite material for the marine growth prevention device of the present invention has excellent mechanical properties and friction resistance, a simple preparation method, no pollution emissions, and can be used in harsh marine environments and for offshore wind power marine growth prevention devices.

[0045] Compared with the prior art, the present invention has at least the following beneficial effects:

[0046] The wear-resistant polyethylene composite material for marine biological prevention device provided by the present invention is synthesized based on UiO-66 (Zr) metal organic framework, and is further coated and modified by linear polyethyleneimine to prepare UiO-66 (Zr) @ PEI, which not only has the high wear resistance of zirconium-based MOF, but also grows a large number of primary and secondary amine groups on the periphery of UiO-66 (Zr) nanoparticles; under the action of the volume-increasing modifier, the mechanical strength and wear resistance of the material are significantly improved, and a special wear-resistant material for offshore wind power marine biological prevention device is obtained, which has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 It is a schematic diagram of the preparation route of the UiO-66(Zr)@PEI wear-resistant filler in the present invention.

[0048] Figure 2 This is a scanning electron microscope photograph of the UiO-66(Zr)@PEI wear-resistant filler prepared in Example 6.

[0049] Figure 3 This is the XRD diffraction spectrum of the UiO-66(Zr)@PEI wear-resistant filler prepared in Example 6.

[0050] Figure 4 This is the infrared spectrum of the UiO-66(Zr)@PEI wear-resistant filler prepared in Example 6. DETAILED DESCRIPTION

[0051] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.

[0052] The present invention is further described in detail below. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.

[0053] The raw materials in the following examples and comparative examples include: zirconium chloride, terephthalic acid, N,N-dimethylformamide, concentrated hydrochloric acid, methanol, ethanol, linear polyethyleneimine (molecular weight 600), analytical grade; polyethylene matrix, 5000S, density 0.94g / cm 3 ; Compatibilizer: polyethylene grafted maleic anhydride, CMG5804; Antioxidant 1010, analytical grade.

[0054] Examples 1 to 6

[0055] Provided is a method for preparing a wear-resistant polyethylene composite material for a marine biological prevention device, the preparation method comprising the following steps:

[0056] S1.1. Preparation of UiO-66(Zr) powder:

[0057] Weigh 2.33g zirconium tetrachloride and 1.66g terephthalic acid with dry weighing paper in a dry and clean 100mL beaker, slowly add 80mL DMF solvent into the beaker along the wall of the beaker, and stir at a uniform speed with a clean glass rod. After stirring for 5 minutes, take 5mL of 6mol / L hydrochloric acid and add it dropwise into the beaker containing the sample, and ultrasonically disperse it for 20 minutes; put the mixed reactants into the reactor and place them in an oven at 120℃ for 24 hours. The obtained product is cooled at room temperature, and then the product is vacuum filtered and washed with DMF at the same time, and the washing is repeated 3-5 times; the washed product is soaked in methanol solution so that the methanol submerges the product, and the methanol solution is changed every 12 hours for 48 hours; the final product is filtered, washed, and placed in a vacuum drying oven at 100℃ for 24 hours to obtain UiO-66 (Zr) powder;

[0058] S1.2, preparation of UiO-66(Zr)@PEI wear-resistant filler:

[0059] The prepared UiO-66(Zr) powder was dissolved in an ethanol solvent and ultrasonically dispersed for 30 minutes; then, linear polyethyleneimine was added at a rate of 30 drops per minute under stirring and ultrasonicated for 30 minutes. The obtained product was cooled at room temperature, washed and filtered with ethanol, and the final product was placed in a vacuum drying oven at 100°C for 24 hours to obtain UiO-66(Zr)@PEI wear-resistant filler;

[0060] S2. Preparation of wear-resistant polyethylene composite materials for marine biological prevention devices:

[0061] The UiO-66(Zr)@PEI wear-resistant filler is mixed with a polyethylene matrix, a polyethylene grafted maleic anhydride as a volume-increasing modifier, and an antioxidant, and injection molding is performed at 175° C. using an injection molding machine to obtain the wear-resistant polyethylene composite material for the anti-marine biological device.

[0062] Comparative Example 1

[0063] This comparative example provides a method for preparing a wear-resistant polyethylene composite material for an anti-marine biological device, and the preparation method comprises the following steps:

[0064] The polyethylene matrix, the polyethylene grafted maleic anhydride as a volume-increasing modifier and the antioxidant are mixed, and injection molding is performed at 175° C. using an injection molding machine to obtain the wear-resistant polyethylene composite material for the anti-marine biological device.

[0065] Comparative Example 2

[0066] This comparative example provides a method for preparing a wear-resistant polyethylene composite material for an anti-marine biological device, and the preparation method comprises the following steps:

[0067] S1.1. Preparation of UiO-66(Zr) powder:

[0068] This step is the same as in Examples 1 to 6;

[0069] S2. Preparation of wear-resistant polyethylene composite materials for marine biological prevention devices:

[0070] 5 parts of UiO-66 (Zr) were mixed with a polyethylene matrix, a polyethylene grafted maleic anhydride as a volume-increasing modifier, and an antioxidant, and injection molding was performed at 175° C. using an injection molding machine to obtain the wear-resistant polyethylene composite material for the anti-marine growth device.

[0071] Comparative Example 3

[0072] This comparative example provides a method for preparing a wear-resistant polyethylene composite material for an anti-marine biological device, and the preparation method comprises the following steps:

[0073] 5 parts of linear polyethyleneimine were mixed with a polyethylene matrix, a polyethylene grafted maleic anhydride as a volume-increasing modifier, and an antioxidant, and injection molding was performed at 175° C. using an injection molding machine to obtain the wear-resistant polyethylene composite material for the anti-marine growth device.

[0074] The mass fractions of the raw materials UiO-66(Zr)@PEI wear-resistant filler, polyethylene matrix, volume-increasing modifier polyethylene grafted maleic anhydride and antioxidant, as well as UiO-66(Zr) powder and linear polyethyleneimine in Examples 1 to 6 and Comparative Examples 1 to 3 are shown in Table 1.

[0075] Table 1

[0076]

[0077]

[0078] In Table 1, “ / ” indicates that the substance was not added. The linear polyethyleneimine content in UiO-66(Zr)@PEI of Examples 1 to 6 is 6%.

[0079] The scanning electron microscope photo of the UiO-66(Zr)@PEI wear-resistant filler prepared in Example 6 is as follows: Figure 2 As shown, it can be seen that the prepared UiO-66(Zr)@PEI has a clear cubic framework nanocrystalline structure with a grain size of about 100-300nm.

[0080] The XRD diffraction spectrum of the UiO-66(Zr)@PEI wear-resistant filler prepared in Example 6 is as follows: Figure 3 As shown, it has obvious peaks at 2θ=7.3, 8.5, 17.1, 25.8, and 30.8°, which is similar to UiO-66, indicating that the coating of linear polyethyleneimine does not change the crystal form of UiO-66(Zr).

[0081] The infrared spectrum of the UiO-66(Zr)@PEI wear-resistant filler prepared in Example 6 is as follows: Figure 4 As shown, linear polyethyleneimine has a peak at 2828 cm -1 , 2943cm -1 and 3280cm -1 The typical absorption peak at indicated that the linear polyethyleneimine coating was successful.

[0082] The wear-resistant polyethylene composite materials for marine growth prevention devices obtained in Examples 1 to 6 and Comparative Examples 1 to 3 were tested for performance, and the results are shown in Table 2. The test method includes:

[0083] The tensile strength is tested according to GB / T1040.1-2006 standard.

[0084] The elongation at break is tested according to GB / T1040.1-2006 standard.

[0085] The bending strength is tested according to GB / T 9341-2008 standard.

[0086] The tribological performance test was conducted using a friction and wear tester at 1500 rpm, room temperature, and 30 minutes.

[0087] Table 2

[0088]

[0089]

[0090] It can be seen from Examples 1 to 6 that under the condition of adding 5 parts of polyethylene grafted maleic anhydride as a volume-enhancing modifier, the elongation at break of the polyethylene matrix with 1 to 6 parts of UiO-66 (Zr) @ PEI wear-resistant filler is greatly improved. When 6 parts of UiO-66 (Zr) @ PEI wear-resistant filler are added, the elongation at break can reach 967.8%. This is because the modification of polyethylene imine allows the prepared UiO-66 (Zr) to be tightly connected to the polyethylene grafted maleic anhydride as a volume-enhancing modifier through a chemical amide bond, and the polyethylene grafted maleic anhydride as a volume-enhancing modifier can be connected to the polyethylene matrix through the polyethylene chain segment, thereby forming a good intermiscibility system with a tightly bonded interface. Correspondingly, with the increase in the content of UiO-66 (Zr) @ PEI wear-resistant filler, the tensile strength and flexural strength are both significantly improved simultaneously, but the increase is not as large as the elongation. The tensile strength increased from 30.99 MPa in Comparative Example 1 to 34.38 MPa in the polyethylene matrix + 6% UiO-66 (Zr) @ PEI in Example 6, and the flexural strength increased from 23 MPa in the pure polyethylene matrix in Comparative Example 1 to 26.5 MPa in the polyethylene matrix + 6% UiO-66 (Zr) @ PEI in Example 6, indicating that the system has significantly improved the strength performance of the polyethylene matrix. At the same time, due to the introduction of wear-resistant materials, the friction coefficient is greatly reduced from 0.25 in the pure polyethylene matrix in Comparative Example 1 to 0.025 in the polyethylene matrix + 6% UiO-66 (Zr) @ PEI in Example 6.

[0091] Examples 1 to 6 show that the addition of UiO-66(Zr)@PEI wear-resistant filler in the present invention not only increases the mechanical properties of the system, but also greatly increases the wear resistance of the material.

[0092] It can be seen from Comparative Examples 1 to 3 that, compared with Comparative Example 1, although the mechanical properties of the material are improved by simply adding UiO-66(Zr) in Comparative Example 2, the mechanical properties and wear resistance are quite different from those of UiO-66(Zr)@PEI. Compared with Comparative Example 1, the mechanical properties of Comparative Example 3, which simply adds linear polyethyleneimine, are not improved, but slightly decreased. Compared with Example 5, which adds the same proportion of UiO-66(Zr)@PEI wear-resistant filler, the friction coefficient of Comparative Examples 2 and 3 increases from 0.03 (Example 5) to 0.09 (Comparative Example 2) and 0.24 (Comparative Example 3).

[0093] Comparative Examples 1 to 3 illustrate that the UiO-66(Zr)@PEI wear-resistant filler prepared by the present invention can simultaneously improve the mechanical properties and friction resistance of the material.

[0094] Example 7

[0095] This embodiment provides a method for preparing a wear-resistant polyethylene composite material for anti-marine devices. The preparation method is the same as that of Example 1, except that the amount of linear polyethyleneimine added in step S1.2 is 0.5% by mass percentage of UiO-66(Zr).

[0096] Example 8

[0097] This embodiment provides a method for preparing a wear-resistant polyethylene composite material for anti-marine devices. The preparation method is the same as that of Example 1, except that the amount of linear polyethyleneimine added in step S1.2 is 8% by mass percentage of UiO-66(Zr).

[0098] In Example 7, due to the small amount of linear polyethyleneimine added, the tensile strength of the wear-resistant polyethylene composite material for anti-marine growth device obtained was 31.15 MPa, the elongation at break was 599.8%, the flexural strength was 23.0 MPa and the friction coefficient was 0.13; in Example 8, due to the large amount of linear polyethyleneimine added, the tensile strength of the wear-resistant polyethylene composite material for anti-marine growth device obtained was 31.20 MPa, the elongation at break was 601.7%, the flexural strength was 23.1 MPa and the friction coefficient was 0.12.

[0099] Example 9

[0100] This embodiment provides a method for preparing a wear-resistant polyethylene composite material for marine biofilm prevention devices. The preparation method is the same as that of Embodiment 1 except that the mass fraction of the polyethylene grafted maleic anhydride as a volume-increasing modifier in step S2 is 1 part.

[0101] Example 10

[0102] This embodiment provides a method for preparing a wear-resistant polyethylene composite material for anti-marine biological devices. The preparation method is the same as that of Embodiment 1 except that the mass fraction of the polyethylene grafted maleic anhydride as a volume-increasing modifier in step S2 is 8 parts.

[0103] In Example 9, due to the small mass fraction of the polyethylene grafted maleic anhydride as a volumetric modifier, the obtained wear-resistant polyethylene composite material for anti-marine growth devices has a tensile strength of 30.09 MPa, an elongation at break of 595.7%, a flexural strength of 21.9 MPa and a friction coefficient of 0.18; in Example 10, due to the large mass fraction of the polyethylene grafted maleic anhydride as a volumetric modifier, the obtained wear-resistant polyethylene composite material for anti-marine growth devices has a tensile strength of 30.34 MPa, an elongation at break of 588.1%, a flexural strength of 23.0 MPa and a friction coefficient of 0.22.

[0104] In summary, the preparation method of the wear-resistant polyethylene composite material for anti-marine biological devices provided by the present invention is simple to operate and has low raw material cost. The prepared material has the advantages of high mechanical strength, good wear resistance and corrosion resistance. It is economical and convenient, and has no pollution emissions. It is suitable for large-scale application in offshore wind power anti-marine biological devices.

[0105] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A wear-resistant polyethylene composite material for anti-marine biological device, characterized in that: The wear-resistant polyethylene composite material for anti-marine biological device comprises UiO-66(Zr)@PEI wear-resistant filler, polyethylene matrix, volume-increasing modifier and antioxidant; the UiO-66(Zr)@PEI wear-resistant filler is based on UiO-66(Zr) metal organic framework and is modified by linear polyethyleneimine; the volume-increasing modifier comprises polyolefin with anhydride group.

2. The wear-resistant polyethylene composite material for anti-marine biological device according to claim 1, characterized in that: The density of the polyethylene matrix is ​​0.94-0.96 g / cm 3 ; Preferably, the compatibilizing modifier comprises polyethylene grafted with maleic anhydride; Preferably, the molecular weight of the linear polyethyleneimine is 300 to 1800; Preferably, the antioxidant includes antioxidant 1010 or antioxidant 168.

3. The wear-resistant polyethylene composite material for anti-marine biological device according to claim 1 or 2, characterized in that: The mass ratio of the UiO-66(Zr)@PEI wear-resistant filler, polyethylene matrix, volume-increasing modifier and antioxidant is (1-6):100:(3-6):0.

1.

4. A method for preparing the wear-resistant polyethylene composite material for marine biological prevention device according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: S1. Preparation of UiO-66(Zr)@PEI wear-resistant filler: UiO-66(Zr) is prepared by reacting zirconium tetrachloride and terephthalic acid, and then UiO-66(Zr) is coated with PEI to obtain UiO-66(Zr)@PEI wear-resistant filler; S2. Preparation of wear-resistant polyethylene composite material for anti-marine growth device: mixing the UiO-66(Zr)@PEI wear-resistant filler with a polyethylene matrix, a volume-increasing modifier and an antioxidant, and performing injection molding using an injection molding machine to obtain the wear-resistant polyethylene composite material for anti-marine growth device.

5. The preparation method according to claim 4, characterized in that: The specific steps of preparing the UiO-66(Zr)@PEI wear-resistant filler in S1 include: S1.1, preparing UiO-66 (Zr) powder: zirconium tetrachloride, terephthalic acid and a first solvent are mixed, and hydrochloric acid with a concentration of 1 to 6 mol / L is added after stirring, and a first ultrasonic treatment, a first drying, a first cooling, a first solid-liquid separation and a first washing are performed in sequence to obtain a washed product; the washed product is immersed in a methanol solution, and a second solid-liquid separation, a second washing and a second drying are performed to obtain UiO-66 (Zr) powder; S1.2, preparation of UiO-66(Zr)@PEI wear-resistant filler: dissolving the UiO-66(Zr) powder in a second solvent, and performing a second ultrasonic treatment; adding linear polyethyleneimine dropwise under stirring, and sequentially performing a third ultrasonic treatment, a second cooling, a third washing, a third solid-liquid separation, and a third drying to obtain the UiO-66(Zr)@PEI wear-resistant filler.

6. The preparation method according to any one of claims 4 or 5, characterized in that: The molar ratio of zirconium tetrachloride to terephthalic acid in S1.1 is 1:1 to 1:3; Preferably, the first solvent comprises DMF solvent; Preferably, the first washing is performed using DMF solvent, and the washing is repeated 3 to 5 times.

7. The preparation method according to any one of claims 4 to 6, characterized in that: The second solvent in S1.2 includes ethanol solvent.

8. The preparation method according to any one of claims 4 to 7, characterized in that: The linear polyethyleneimine in S1.2 has a drop rate of 20 to 40 drops per minute; Preferably, the amount of linear polyethyleneimine added is 1% to 6% by mass of UiO-66(Zr).

9. The preparation method according to any one of claims 4 to 8, characterized in that: The preparation method comprises the following steps: S1.1, preparing UiO-66 (Zr) powder: zirconium tetrachloride, terephthalic acid and DMF solvent are mixed, and hydrochloric acid with a concentration of 1 to 6 mol / L is added after stirring, and the mixture is subjected to a first ultrasonic treatment, a first drying, a first cooling, a first solid-liquid separation, and a first washing with a DMF solvent, and the washing is repeated 3 to 5 times to obtain a washed product; the washed product is immersed in a methanol solution, and a second solid-liquid separation, a second washing and a second drying are performed to obtain UiO-66 (Zr) powder; the molar ratio of zirconium tetrachloride to terephthalic acid is 1:1 to 1:3; S1.2, preparation of UiO-66 (Zr) @ PEI wear-resistant filler: dissolving the UiO-66 (Zr) powder in an ethanol solvent, and performing a second ultrasonic treatment; adding linear polyethyleneimine at a rate of 20 to 40 drops per minute under stirring, and sequentially performing a third ultrasonic treatment, a second cooling, a third washing, a third solid-liquid separation and a third drying to obtain the UiO-66 (Zr) @ PEI wear-resistant filler; the amount of the linear polyethyleneimine added is 1% to 6% by mass of UiO-66 (Zr); S2. Preparation of wear-resistant polyethylene composite material for anti-marine growth device: mixing the UiO-66(Zr)@PEI wear-resistant filler with a polyethylene matrix, a volume-increasing modifier and an antioxidant, and performing injection molding using an injection molding machine to obtain the wear-resistant polyethylene composite material for anti-marine growth device.

10. Use of the wear-resistant polyethylene composite material for marine growth prevention devices according to any one of claims 1 to 3 in offshore wind power marine growth prevention devices.

Citation Information

Cited By

  • Core-shell structure MOF material capable of selectively adsorbing rhenium and preparation method and application of rhenium adsorbing material

    CN120939919A